The Effect of Inventory Intensity, Sales Growth, and Capital Structure on Tax Aggressiveness - Kurniasih, Lisna; Irawati, Wiwit (EAJ (Economic and Accounting Journal), 2025)
The objective of this study is to assess how inventory levels, sales growth, and capital structure influence tax rates. The sample consisted of 105 data points from 21 companies within the energy sector that were listed on the IDX between 2018 and 2022, drawn from a total population of 74 companies through intentional selection. Descriptivelstatisticslandlpanelldatalregressionlanalysis were utilized as the data analysis techniques, employing the Eviews 12 Student Version Lite software. Results from this research reveal that, when considered together, inventory volume, sales growth, and capital structure significantly affect tax aggressiveness. However, on an individual basis, neither inventory quantity nor sales growth significantly influences tax rates, while the capital structure does exhibit a partially significant impact on tax intensity.